Analisis Dampak Jangka Panjang Merger Dan Akuisisi Terhadap Kinerja Keuangan Perusahaan - Iqbal Fernandez; Irfan Mahesa (Arsil Media, 2023)
Financial distress is an unstable company condition, where the company has a lack of funds to pay its obligations. This instability can cause the company to lead to bankruptcy. According to Hariyani (2011) & Aprilita (2013) the success of M&A can be influenced by the state of the company in a good position. Chen, An-Shing, et al. (2018) stated that companies with low financial distress have more opportunities to achieve M&A success.